Training of Integration of Literature in Logotherapy-Based English Lessons for Member of The Pekalongan High School English Teachers' Working Group (MGMP) - Susanto, Susanto; Dewanto, Aji Cokro; Sidqi, M. Fajru (Jurnal Abmas Negeri (JAGRI), 2025)
A training on integrating literature into English language teaching based on logotherapy is essential for English Subject Teachers' Working Group (MGMP) members in Pekalongan City to enhance their pedagogical competence in student instruction. The main objective of this activity was to respond to the needs of teachers' who showed a positive attitude toward the use of literary texts, but were still limited in their ability to interpret such texts beyond moralistic or literal meanings. A needs analysis was conducted through questionnaires to explore teachers' perceptions, experiences, and obstacles related to the use of literature in the curriculum. The training was carried out in five sessions, beginning with an introduction to the philosophical foundations of logotherapy and existentialist education, followed by discussions on the role of literature in meaningful learning. The practical sessions involved critical interpretation of the folktale Malin Kundang, modification of the narrative to emphasize existential dilemmas, and the development of interactive language skills activities (listening, reading, writing, and speaking). The results showed that the training helped expand the teachers' understanding of how literature can be used not only to enhance language competence but also to develop students’ self-awareness, empathy, and character. The conclusion highlights that the integration of literature and logotherapy principles has the potential to transform the English classroom into a space for personal growth and existential reflection, making language learning both meaningful and transformative.